Tracking morning fatigue status across in-season training weeks in elite soccer players - Thorpe, R. T.; Strudwick, A. J.; Buchheit, M.; Atkinson, G.; Drust, B.; Gregson, W. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To quantify the mean daily changes in training and match load and any parallel changes in indicators of morningmeasured fatigue across in-season training weeks in elite soccer players. Methods: After each training session and match (TL), session ratings of perceived exertion (s-RPE) were recorded to calculate overall session load (RPE-TL) in 29 English Premier League players from the same team. Morning ratings of fatigue, sleep quality, and delayed-onset muscle soreness (DOMS), as well as submaximal exercise heart rate (HRex), postexercise heart-rate recovery (HRR%), and heart-rate variability (HRV) were recorded before match day and 1, 2, and 4 d postmatch. Data were collected for a median duration of 3 wk (range 1-13) and reduced to a typical weekly cycle including no midweek match and a weekend match day. Data were analyzed using withinsubject linear mixed models. Results: RPE-TL was approximately 600 arbitrary units (AU) (95% confidence interval 546-644) higher on match day than following day (P < .001). RPE-TL progressively decreased by »60 AU per day over the 3 days before a match (P < .05). Morning-measured fatigue, sleep quality, and DOMS tracked the changes in RPE-TL, being 35-40% worse on postmatch day vs prematch day (P < .001). Perceived fatigue, sleep quality, and DOMS improved by 17-26% from postmatch day to 3 d postmatch, with further smaller (7%-14%) improvements occurring between 4 d postmatch and prematch day (P < .01). There were no substantial or statistically significant changes in HRex, HRR%, or HRV over the weekly cycle (P > .05). Conclusions: Morning-measured ratings of fatigue, sleep quality, and DOMS are clearly more sensitive than HR-derived indices to the daily fluctuations in session load experienced by elite soccer players in a standard in-season week.